2020
DOI: 10.21203/rs.3.rs-92193/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burnout and Stress Among Emergency Physicians in the Kingdom of Bahrain Using the Copenhagen Burnout Inventory (CBI) and Short Form-stress Overload Scale (SOS-S)

Abstract: Background: Emergency physicians (EPs) are exposed to various stressors that lead to burnout, and these factors have never been examined in the emergency departments (EDs) of the Kingdom of Bahrain. The study identifies the prevalence rates and associated variables for burnout and stress among EPs in Bahrain’s EDs.Methods: A cross sectional study involving 134 EPs working in the ED for the three major tertiary hospitals completed the Copenhagen Burnout Inventory (CBI) and Stress Overload Scale-Short Form (SOS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Increasing working hours per week was associated with higher levels of emotional exhaustion among Egyptian HCPs similar to that reported in Galván 41 and Hathout 30 studies and to the levels of patient-related burnout reported among emergency physicians working > 40 h using the Copenhagen tool 10 . While the increasing hours were found not significantly different in another study 20 .…”
Section: Discussionsupporting
confidence: 83%
“…Increasing working hours per week was associated with higher levels of emotional exhaustion among Egyptian HCPs similar to that reported in Galván 41 and Hathout 30 studies and to the levels of patient-related burnout reported among emergency physicians working > 40 h using the Copenhagen tool 10 . While the increasing hours were found not significantly different in another study 20 .…”
Section: Discussionsupporting
confidence: 83%
“…Increasing working hours per week was associated with higher levels of emotional exhaustion among Egyptian HCPs similar to that reported in Galván 52 and Hathout 42 studies and to the levels of patientrelated burnout reported among emergency physicians working > 40 hours using Copenhagen tool. 10 While the increasing hours were found not signi cantly different in another study. 32 It was found that from the reasons behind the psychological consequences caused by the pandemic to HCPs were working more hours than usual that can be exceeded to making double shifts.…”
Section: Discussionmentioning
confidence: 75%
“…Long term contact with patient and development of family-like relations may also result in emotional detachment and burnout. 6,9,10 The consequences of burnout affect HCPs, patients and organizations. Consequences on HCPs include the potential unemployment, early retirement or career termination, sickness, injury, accidents, nancial loss, more family and personal relationship con icts, decreased job satisfaction, poor health outcomes such as depression, frequent headaches, insomnia, anxiety and becoming offensive or violent at work with higher suicide rates.…”
Section: Introductionmentioning
confidence: 99%